Synthesis of soluble calcium compound from skipjack tuna bones using edible weak acids - Chakkapat Aenglong; Yu-Ming Wang; Maruj Limpawattana; Wanida Sukketsiri; Qing-Juan Tang; Wanwimol Klaypradit; Soraya Kerdpiboon (My University, 2022)
This study aimed to enhance the water solubility of calcium from tuna (Katsuwonus pelamis) bones (TB). Calcium hydroxyapatite (HA) was obtained by calcination of TB. For mineral profiles of TB and HA, Ca had the highest content followed by P with Ca/P of 3.47 and 1.94. Mg, K, and Na as macro minerals and Cr, Cu, Mn, and Zn as micro minerals were also found. Subsequently, HCl was applied to form structured HA-chloride compound (HA-Cl) then reacted with alkaline to obtain structured HA-hydroxide compound (HA-OH). In order to enhance the water solubility, citric and lactic acid were individually reacted with HA-Cl and HA-OH to obtain structured HA-citrate compounds (HA-Cl-Ci and HA-OH-Ci) and structured HA-lactate compounds (HA-Cl-Lac and HA-OH-Lac). HA-Cl-Ci had the highest water solubility (93.34 ± 0.45%) followed by HA-OH-Lac (90.35 ± 0.23%) with Ca/P ratio of 2.28 and 2.24, respectively. HA-Cl-Ci and HA-OH-Lac demonstrated the similar mineral profiles to those of HA but with different contents. The results of FT-IR indicated the carboxyl group of acid played an important role in binding Ca2+. X-ray diffractograms indicated that calcined bone was HA whereas the major composition of HA-Cl-Ci and HA-OH-Lac was related to calcium citrate tetrahydrate and calcium lactate pentahydrate, respectively.
Keywords: Calcium Carbonate Crystallization and Inhibition